Safe and Standard Thyroid Cancer Surgery, or Lack Thereof: Patterns and Correlates of Patient Referral to Tertiary Care Centre for Revision Thyroid Surgery in a LMIC - Barua, Sunil Malla Bujar; Yadav, Sanjay Kumar; Aggarwal, Vivek; Mishra, Anjali; Mishra, Saroj Kanta; Chand, Gyan; Agarwal, Gaurav; Agarwal, Amit (South Asian Journal of Cancer, 2022)
Background A surgeon's characteristics such as volume and practice setup are essential elements in outcome of thyroid cancer. However, little information is available from the developing world regarding qualities of primary surgeon, such as level of knowledge, skill, and proper documentation while referring to higher center.Methods Records of 164 patients of differentiated thyroid cancer (DTC) from January 1990 to December 2018 undergoing revision thyroid surgery following primary surgery elsewhere were retrospectively analyzed.Results Out of 164 patients with postoperative diagnosis of DTC, referral patterns were as follows: low volume (LV) to high volume (HV) (n = 120, 73.2%), followed by HV to HV (n = 44, 26.8%). The primary surgery assessed by the extent of residual disease was in agreement with the documentation in only 55%. The type of thyroidectomy performed was not mentioned in 9.8%. The status of the parathyroid glands was mentioned only in 15.8% and recurrent laryngeal nerve in 12.2%. Less than recommended surgery was performed in 52.5% patients. Despite less than recommended surgery, 44.5% patients were directly referred for radioactive iodine ablation (RAIA). Thirty two percent patients were referred for RAIA after hemithyroidectomy. Central or lateral compartment lymphadenectomy, even after indication, was less likely at LV centers (risk ratio [RR], 0.71; 95% confidence interval [CI], 0.64–0.77). Similarly, for DTC patients, the relationship between LV center surgery and subsequent referral for RAIA was RR, 0.71 (95% CI, 0.48–1.02).Conclusions Most patients referred from LV surgeons are less likely to have proper thyroidectomy, have inadequate documentation of the primary surgery, and are referred for RAIA after less than total thyroidectomy. Our study highlights the lacunae in the approach to and understanding of thyroid cancer surgery by secondary care physicians in our country. We believe that there is an urgent necessity of educational reform and training to rectify this problem.
Keywords: differentiated thyroid cancer; re-operative surgery; LMIC